EVALUATION OF MOLECULAR VARIATION OF MUTATED PEANUT LINES BY SSR MARKERS - Phòng, Đinh Thị; Giang, Ngô Thị Lam (Vietnam Journal of Science and Technology, 2012)
SUMMARY Eleven SSR markers were used to analyse molecular variation of 24 mutated peanut lines (eight originated from VD2 variety and 16 from L9801 variety). Overall, 8 out of 11 used markers revealed polymorphism with Polymorphic Information Content (PIC) values from 0.44 (L41) to 0.85 (L32), in which 7 markers showed the high level of polymorphism with PIC values ³0.5. The number of amplified DNA fragments ranged from 1 to 9 per marker with sizes ranging approximately from 120 bp to 360 bp. The genetic dissimilarity coefficients analysis showed that among 8 mutated peanut lines, VD2-1-1, VD2-1-2 and VD2-1-3 lines were identical but 4% different from VD2 variety (1-0.96). It is 27% (1-0.73) between VD2-2-3 and VD2-2-4 lines, and VD2 variety. Compare 16 mutated peanut lines and the parent variety L9801, the genetic dissimilarity coefficient values ranged from 9% to 45%, in which L9801-2-2 line had the least different with about 9% (1-91), L9801-3-4 line was the most difference in genetic about 45% (1-0,55). L981-1-2 and L9801-2-1 lines, L9801-3-1 and L9801-4-1 lines were identical. Keywords. DNA polymorphism, mutated peanut, SSR markers, Genetic coefficient